Bridging the Urban Transport Paradox: Transit-Oriented Development and the Integrated Low-Carbon Mobility Framework (ILCMF) for Metropolitan Jabodetabek - Banjarnahor, Astri Rumondang; Simarmata, Juliater; Yosafat, Andre (Baca Dulu Publisher, 2025)
The transportation sector is one of the largest contributors to global carbon emissions and represents a major challenge in the urban decarbonization agenda. In Indonesia, transportation accounts for approximately 27% of total national emissions, with the Greater Jakarta (Jabodetabek) metropolitan area being the highest contributor due to high daily mobility, urban sprawl, and governance fragmentation. This study aims to analyze the role of Transit-Oriented Development (TOD) as a systemic strategy in supporting the transition toward low-carbon mobility and to develop a conceptual model called the Integrated Low-Carbon Mobility Framework (ILCMF). The study identifies four key dimensions in the decarbonization of transportation — environmental, institutional, technological, and social — that interact to shape a sustainable urban mobility system. The findings reveal that the success of low-carbon mobility transformation depends on cross-sectoral policy integration, the electrification of public transport, and community participation in mobility behavior change. The ILCMF provides an integrative framework for metropolitan transportation policymaking that is efficient, inclusive, and aligned with Indonesia’s Net Zero Emission 2060 target.